Dynamic thresholds and a summary ROC curve: Assessing prognostic accuracy of longitudinal markers - Saha‐Chaudhuri, P.; Heagerty, P. J. (Statistics in medicine, 2018)
Cancer patients, chronic kidney disease patients, and subjects infected with HIV are routinely monitored over time using biomarkers that represent key health status indicators. Furthermore, biomarkers are frequently used to guide initiation of new treatments or to inform changes in intervention strategies. Since key medical decisions can be made on the basis of a longitudinal biomarker, it is important to evaluate the potential accuracy associated with longitudinal monitoring. To characterize the overall accuracy of a time‐dependent marker, we introduce a summary ROC curve that displays the overall sensitivity associated with a time‐dependent threshold that controls time‐varying specificity. The proposed statistical methods are similar to concepts considered in disease screening, yet our methods are novel in choosing a potentially time‐dependent threshold to define a positive test, and our methods allow time‐specific control of the false‐positive rate. The proposed summary ROC curve is a natural averaging of time‐dependent incident/dynamic ROC curves and therefore provides a single summary of net error rates that can be achieved in the longitudinal setting.